2015
DOI: 10.1186/s12957-015-0572-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumor regression in rectal cancer after intensified neoadjuvant chemoradiation: a morphometric and clinicopathological study

Abstract: BackgroundHigh interobserver variation is a well known drawback of conventional tumor regression grading, and reaching consensus among pathologists may require a considerable effort. Therefore, in this study, morphometry was tried to assess tumor regression, and its prognostic role was explored.MethodsTumor regression was quantified by a point counting method to yield tumor area fraction (TAF) as an index of remaining vital tumor.ResultsIn a series of 104 patients with clinically advanced rectal cancer treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the present study, a capecitabine-containing regimen was used for nCRT and adjuvant chemotherapy (capecitabine based CT). Several studies (12,16,17) have shown that early TRG downstaging can predict patient prognosis with comparable performance for OS and DFS. Based on these data, we attempted to identify the clinicopathological characteristics at baseline that are likely to be associated with tumor downstaging.…”
mentioning
confidence: 99%
“…In the present study, a capecitabine-containing regimen was used for nCRT and adjuvant chemotherapy (capecitabine based CT). Several studies (12,16,17) have shown that early TRG downstaging can predict patient prognosis with comparable performance for OS and DFS. Based on these data, we attempted to identify the clinicopathological characteristics at baseline that are likely to be associated with tumor downstaging.…”
mentioning
confidence: 99%